2015
DOI: 10.1016/j.nuclphysb.2015.04.024
|View full text |Cite
|
Sign up to set email alerts
|

On dynamical realizations of l-conformal Galilei and Newton–Hooke algebras

Abstract: In two recent papers (Aizawa et al., 2013 [15]) and (Aizawa et al., 2015 [16]), representation theory ofthe centrally extended l-conformal Galilei algebra with half-integer l has been applied so as to constructsecond order differential equations exhibiting the corresponding group as kinematical symmetry. It wassuggested to treat them as the Schrodinger equations which involve Hamiltonians describing dynamicalsystems without higher derivatives. The Hamiltonians possess two unusual features, however. First, they… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 17 publications
(60 reference statements)
0
9
0
1
Order By: Relevance
“…where α(y) is a function to be fixed below and ǫ = ±1. It is assumed that y remains intact under the l-conformal Galilei transformations so that the metric maintains the symmetry of its predecessor (18). One could promote k n in (19) to become real functions k n (y) as well.…”
Section: Maurer-cartan One-forms For the L-conformal Galilei Algebramentioning
confidence: 99%
“…where α(y) is a function to be fixed below and ǫ = ±1. It is assumed that y remains intact under the l-conformal Galilei transformations so that the metric maintains the symmetry of its predecessor (18). One could promote k n in (19) to become real functions k n (y) as well.…”
Section: Maurer-cartan One-forms For the L-conformal Galilei Algebramentioning
confidence: 99%
“…The remarkable property of the particles, which described by (19), (20), is that their motion is bounded. According to (17), one and the same eigenvalues of the matrix (15) appear for different values of parameter l. Therefore, one can realize different l-conformal Galilei algebras in one and the same system of equations. For example, the system (1a), (6) may accommodate l-conformal Galilei symmetry for any integer l > 2.…”
Section: The Case Of Arbitrary Lmentioning
confidence: 99%
“…Recently, symmetries of these higher-derivative models have been extensively studied 13,14,[16][17][18][19][20][21][22][23] . In particular it has been shown that the l-conformal Galilei group is the maximal symmetry group of the free (2l + 1)-order particle 14 .…”
Section: Introductionmentioning
confidence: 99%